Internalisasi Nilai-Nilai Islam Pada Mata Pelajaran Sains : (Studi Sekolah Dasar Negeri 002 Sebatik Utara) - Sarinah; Rasmi Nur Hidayah; Nur Aminah; Nuraini (Yayasan Syamil Quran Nunukan, 2024)
The aim of this research is to describe the internalization of Islamic values ​​in science subjects with the object at State Elementary School 002 Sebatik Utara. The method used in this research is a case study which involves the main instrument, namely the interactions that occur with the research subjects, namely teachers and students in science learning. The research results show that instilling Islamic values ​​requires time to become a habit for students. The process of internalizing Islamic teachings can be seen from the actions of students who practice the teachings of their religion and love the natural environment around them. Teachers use various methods to foster a love of nature, for example playing by getting to know nature in which Islamic values ​​are inserted by always presenting an attitude of gratitude for Allah Swt's creation. and teaches that there is a symbiotic relationship between human life and the natural environment. This is all in order to form the character of religious students who love their natural environment.